Entrepreneurial Orientation and Customer Satisfaction in Institutes of Higher Education - Vahideh Tabasi Lotfabadi (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2019)
Link to publisher's homepage at http://ijbt.unimap.edu.my